Towards climate resilience in agriculture for Southeast Asia: an overview for decision-makers. - Gonsalves, Julian Francis; Campilan, D.; Smith, Georgina; Bui, VL; Jiménez, F.M. (International Center for Tropical Agriculture, 2015)
This sourcebook, and accompanying poster learning series, is aimed at policy makers, planners in government, local research administrators, civil society partners and researchers in Southeast Asia. Compiled and repackaged by Dr. Julian Gonsalves and a resource team, the Climate-Smart Agriculture (CSA) source book draws from a rich pool of literature from over 700 sources. The compilation provides succinct, relevant and timely information about climate challenges, and potential solutions from previously published work in a simplified or a shortened form from around the world. While the focus is on challenges specific to Southeast Asia, solutions may come from, or already have been tested elsewhere; it is for this reason that articles from around the world have been included, to demonstrate that adaptation efforts are already being implemented, and a wide range of approaches and strategies are available. This resource seeks to bridge the gap between what policy makers know, and what research shows can work on the ground to improve adaptation, increase productivity, enhance livelihoods, and contribute to sustainable development affected by climate change. The related poster series can be found here: http://hdl.handle.net/10568/71099.